Divine institutes - Lactantius, Lucius Coelius Fermianus, 250-317 (Translated texts for historians ;, 2003)
The Divine Institutes of Lactantius was a vigorous riposte to pagan criticism and persecution of Christianity, which came to a head in the ‘Great’ Persecution of Diocletian in the early fourth century AD. This edition has been prepared with students and scholars of intellectual history in mind, but it will also appeal to those concerned with ecclesiastical history and patristics, and to anyone interested in tracing the impact of classical philosophy and literature on an early Christian thinker.